Policy Strategy of Business Profit (SHU) Through Business Volume Using Number of Members and Capital - Tini Kartini; Danu Suryani; Herdiyana; Masnur Mukmin (Universitas Djuanda, 2021)
This study aims to examine the effect of the number of members and own capital on business volume and SHU, as well as the SHU policy strategy. The research method used is an explanatory survey with the type of verification research. While the sampling technique used purposive sampling in order to obtain 12 KPRI PKPRI members according to predetermined criteria. The analysis technique uses path analysis supported by quantitative and qualitative data. The quantitative data used is in the form of the Annual Member Meeting (RAT) report book for the 2015-2019 period. The results showed that the direct effect of the number of members on business volume had no positive and significant effect. The direct effect of own capital on business volume had a positive and significant effect. The direct effect of the amount on SHU has a negative and significant effect. The direct effect of own capital on SHU has a positive and significant effect. The direct effect of business volume on SHU has a positive and significant effect. The indirect effect of the number of members on SHU through business volume has a positive and significant effect. The indirect effect of own capital on SHU through business volume has a positive and significant effect. Total determinants for the first and second models, namely 43.70% and 62.80% of the overall model which can explain the effect of exogenous variables on endogenous variables. Meanwhile, the remaining 56.30% and 37.20% were influenced by other factors not examined. This study aims to examine the effect of the number of members and own capital on business volume and SHU, as well as the SHU policy strategy. The research method used is an explanatory survey with the type of verification research. While the sampling technique used purposive sampling in order to obtain 12 KPRI PKPRI members according to predetermined criteria. The analysis technique uses path analysis supported by quantitative and qualitative data. The quantitative data used is in the form of the Annual Member Meeting (RAT) report book for the 2015-2019 period. The results showed that the direct effect of the number of members on business volume had no positive and significant effect. The direct effect of own capital on business volume had a positive and significant effect. The direct effect of the amount on SHU has a negative and significant effect. The direct effect of own capital on SHU has a positive and significant effect. The direct effect of business volume on SHU has a positive and significant effect. The indirect effect of the number of members on SHU through business volume has a positive and significant effect. The indirect effect of own capital on SHU through business volume has a positive and significant effect. Total determinants for the first and second models, namely 43.70% and 62.80% of the overall model which can explain the effect of exogenous variables on endogenous variables. Meanwhile, the remaining 56.30% and 37.20% were influenced by other factors not examined.